2021
DOI: 10.1159/000521619
|View full text |Cite
|
Sign up to set email alerts
|

L-Ascorbic Acid and Curcumin Prevents Brain Damage Induced via Lead Acetate in Rats: Possible Mechanisms

Abstract: Lead acetate (lead ac.) is a widespread ecological toxicant that can cause marked neurotoxicity and decline in brain functions. This study aimed to evaluate the possible neuroprotective role of L-ascorbic (ASCR) and curcumin (CRCM) alone or together against lead ac.-induced neurotoxicity. Rats were injected with lead ac. then treated orally with ASCR and CRCM alone or in combination for seven days. Lead ac. caused elevation in brain tumor necrosis factor- α (TNF-α), interleukin-6 (IL-6), caspase-3, and malondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As a result, the levels of pro-inflammatory factors in cells are lowered. It has been described that ascorbate (500 mg/day) significantly reduces IL-6 and TNF-α levels in brain tissue [ 138 ] and inhibits IL-6 protein release from a contracting skeletal muscle [ 139 ]. Moreover, ascorbic acid significantly downregulates the expression of pro-inflammatory factors (IL-6, IL-12, and TNF-α) and upregulates anti-inflammatory cytokines (IL-4 and IL-10) [ 140 ] in mouse splenocytes.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…As a result, the levels of pro-inflammatory factors in cells are lowered. It has been described that ascorbate (500 mg/day) significantly reduces IL-6 and TNF-α levels in brain tissue [ 138 ] and inhibits IL-6 protein release from a contracting skeletal muscle [ 139 ]. Moreover, ascorbic acid significantly downregulates the expression of pro-inflammatory factors (IL-6, IL-12, and TNF-α) and upregulates anti-inflammatory cytokines (IL-4 and IL-10) [ 140 ] in mouse splenocytes.…”
Section: Anti-inflammatory Propertiesmentioning
confidence: 99%
“…Hence, ascorbic acid consumption could inhibit apoptosis in the hippocampus of diabetic rats by regulating Bcl2 and Bax expression. Based on these studies, the antioxidant properties of ascorbic acid prevented the apoptosis process (Alhusaini et al, 2022; Hsueh et al, 2020; JafariAnarkooli et al, 2007; Marik, 2018; Nam et al, 2018; Vineetha et al, 2018). Therefore, it could be concluded that antioxidant supplementation might eliminate free radicals and improve the antioxidant defense system's ability, leading to apoptosis inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, ascorbic acid consumption could inhibit apoptosis in the hippocampus of diabetic rats by regulating Bcl2 and Bax expression. Based on these studies, the antioxidant properties of ascorbic acid prevented the apoptosis process (Alhusaini et al, 2022;Hsueh et al, 2020;JafariAnarkooli et al, 2007;Marik, 2018;Nam et al, 2018;Vineetha et al, 2018).…”
Section: Physical Activity and Consumption Of Vitamins E And C Modifi...mentioning
confidence: 99%